The CERIC method plus social collaborative annotation improves critical reading of the primary literature in an interdisciplinary graduate course - Bjorn, Genevive (Frontiers in Education, 2024)
Background Innovative approaches to graduate education that foster interdisciplinary learning are necessary, given the expansion of interdisciplinary research (IDR) and its ability to explore intricate issues and cutting-edge technology. Purpose This study examines an intervention to develop critical reading skills of the primary literature (CRPL), which are often assumed and unaided by formal instruction in graduate education (GE) yet are crucial for academic success and adapting to new research fields. Methods This study applied mixed methods and a pre-post design to assess the effectiveness of a CRPL intervention among 24 doctoral students from diverse fields engaging in the interdisciplinary field of science policy research. The intervention was a 4-week online course with explicit instruction in a categorical reading approach, the CERIC method (claim, evidence, reasoning, implications, and context), combined with social collaborative annotation (SCA) to facilitate low-stakes, peer-based discourse practice. It examined how participation changed participants’ CRPL skills and self-perceptions. Results The intervention significantly improved CRPL, t(23) = 13.6, p < 0.0001; research self-efficacy, t(23) = 4.9, p < 0.0001; and reading apprehension, t(23) = 4.3, p < 0.0001. Qualitative findings corroborated these findings and highlighted the importance of explicit CRPL instruction and the value of reading methods applicable to IDR. These results aligned with sociocultural and social cognitive theories and underscored the role of discourse and social engagement in learning critical reading, which is traditionally viewed as a solitary activity. Conclusion The findings present a valid and innovative model for developing CRPL skills in interdisciplinary GE. This approach provides a model for scaffolding CRPL that can be adapted to IDR contexts more broadly. Implications The study findings call for revising graduate curricula to incorporate explicit CRPL instruction with peer-based discourse, emphasizing integrations in higher education anywhere students encounter primary literature. The findings advocate for formal and informal adoption of the reviewed methods, offering a significant contribution to interdisciplinary GE pedagogy.